Professional development needs analysis of secondary mathematics teachers in Zanzibar, Tanzania - Mohamed, Siti Hamad (2013)
Teacher’s professional development needs analysis is the systematic process to examine the strengths and weaknesses of teachers regarding mathematics teaching in their career development as professional mathematics teachers. Analysis on mathematics teachers professional development needs leads to improvement of teacher knowledge, teacher practice and thus student outcomes on mathematics performance. This study aimed to investigate professional development needs of secondary school mathematics teachers in Zanzibar, Tanzania which is located in East Africa. Specifically, this study assessed professional development of mathematics teachers in Zanzibar in relation to current mathematics education curriculum and its implementation. The descriptive research design was employed and two types of survey data were obtained through administering of questionnaire and also interviews. Total number of 191 (54.41 %) of mathematics teachers in Zanzibar from 78 secondary schools were stratified cluster sampled from all (10) districts. Mathematics Teacher Professional Development Needs Analysis questionnaire was used to access information on seven professional development subscales namely, planning of mathematics instruction,delivering mathematics instruction, managing mathematics instruction, selfimprovement in pedagogical knowledge, self-improvement in content knowledge,communication skills in English Language, and use of Information Communication and Technology (ICT) in mathematics teaching. The findings of the research show that all subscales were at moderate need with mean values ranging from 3.16 to 3.49, except on teacher self-improvement of content knowledge subscale which showed strong need (mean=3.54, SD=.49). The top needed subscale of professional development needs was on self-improvement in content knowledge (mean=3.54, SD=.49) followed by use of ICT in mathematics teaching (mean=3.49, SD=.5). The relatively least needed subscales were aspect on delivery of mathematics instruction (mean=3.16, SD=.44) and planning of mathematics instructions (mean=3.20, SD=.51). Comparison of mathematics teacher professional development need subscales on years of teaching experience shows that only five subscales were statistically significant different (using ANOVA test). The test statistics for subscales are as follows: Planning mathematics instruction, F (3, 187) = 5.708, p = 0.001, delivering mathematics instruction, F (3, 187) = 3.309, p=0.02, use of ICT in mathematics teaching needs, F (3, 187) = 3.48, p=0.017, teacher self-improvement on pedagogical knowledge, F (3, 187) = 3.569, p=0.015 and teacher self-improvement on content knowledge, F (3, 187)= 4.323, p =0.006. On the other hand, there were no statistically significant differences for the remaining subscales: Managing mathematics instruction, F (3, 187) = 1.611,p =0.611 and communication skills in English Language need, F (3, 187) = 2.301,p=0.079. In addition, mathematics teachers’ professional development needs subscales were also compared on school locality (rural and urban) and gender using independent ttest. The findings showed that there was significant difference in planning of mathematics instruction subscale, t (189) = -2.14, p = 0.03 between teachers in rural and urban locality. In addition, there was significant difference in mathematics teachers professional development needs on delivering of mathematics instruction, t(189) = -2.34, p =0.02.The descriptive analysis further indicates that the dominant constraints for mathematics teachers professional developments were limited professional development courses, seminars and workshops whereby 84 (44.0%) respondents agreed to the matter, followed by lack of financial support whereby 59 (30.4%) agreed on it, and on time conflicts in which 16 (8.4 %) agreed on the matter. The results generated from this study provide an extensive assessment of mathematics teachers professional development needs for Zanzibar, Tanzania. This is a milestone regarding to the quality of mathematics education in Zanzibar and Tanzania at large,which is one of the engine of the country’s sustainable development specifically in developing mathematically literate and competent citizen.